STEM Multimedia to Stimulate HOTS in Renewable Energy Material - Diansah, Irani; Febriyani, Uun; Anggalia, Fransisca; Negara, Hasan Sastra; Firmansah, Deri (Indonesian Journal of Science and Mathematics Education, 2023)
The rapid advancement of technology in the 21st century demands students to master Higher-Order Thinking Skills (HOTS) to face global challenges. This study aims to develop a multimedia-based STEM learning tool to stimulate HOTS in physics, particularly renewable energy topics focusing on hydro and wind energy. The research employs the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) to create and test the multimedia’s validity, practicality, and effectiveness. Data were collected using expert validation sheets, teacher and student questionnaires, and HOTS assessment tests. Results indicate that the multimedia is valid, practical, and effectively enhances students' HOTS. This study highlights the potential of STEM-based multimedia in providing engaging and meaningful learning experiences, particularly in abstract physics topics. These findings have implications for developing innovative learning strategies following the 2013 curriculum, emphasizing developing critical and creative thinking skills.